Laju Pertumbuhan Belut Sawah (Monopterus albus Zuiew) dengan Pemberian Berbagai Pakan - Tulusya Fujiani; Efrizal Efrizal; Resti Rahayu (Universitas Andalas, 2015)
This experiment aimed to determine growth rate of farm swamp eel under various food supply. The experiment used Completely Random Design (CRD) with four treatments and three replications. The treatments were various food supply i.e: earthworms, snails, floating pellets and sinking pellets. The results showed that various foods gave significant difference on the growth rate of the eel in term of absolute weight, daily growth, food conversionand food efficiency. There were nosignificant difference on absolute length and survival rate of the eel. The highest value of the absolute weight and daily growth during 60 days feeding was found at feeding earthworm. The highest value of food efficiency and food conversion was found at feeding sinking pellets. Keyword: swamp eel, physiology, growth, food.